Strategi Guru dalam Mengintegrasikan Permainan Tradisional pada Pembelajaran PKn Berbasis Etnopedagogi di MI Tarbiyatusy Syubban Kalimulyo Jakenan Pati - Dera Emilia Prastiwi; Syaicha Akmala; M. Agus Maksum; Husni Mubarok (https://journal.metanusantara.com/pedagogia, 2026)
Civic education learning in elementary schools often faces challenges in the form of a less contextual approach and a weak approach in internalizing Pancasila values. On the other hand, traditional games as part of local wisdom are increasingly displaced by digital culture, even though they contain civic character values. This study aims to describe teachers' strategies in integrating traditional games in Civic education learning based on ethnopedagogical approaches. The research used a descriptive qualitative design with data collection through observation, interviews, and documentation, then analyzed using the Miles, Huberman, and Saldana analysis model with triangulation of sources and techniques. The results of the study show that teachers apply three sustainable strategies, namely: (1) adaptive planning strategies through modification of teaching modules from the Merdeka Mengajar platform accompanied by an analysis of local wisdom values; (2) experiential learning-based implementation strategies that include perception, demonstration, collaborative exploration, and reflection; and (3) authentic evaluation strategies that measure three domains through formative and summative assessments. The integration of traditional games succeeded in internalizing the values of Pancasila which was confirmed by the increase in student learning motivation and the transfer of values to the social environment outside the school.